Multifunctional Hydrogels for the Healing of Diabetic Wounds - Xiang, Tao; Guo, Qianru; Jia, Lianghao; Yin, Tianyu; Huang, Wei; Zhang, Xinyu; Zhou, Shaobing (Advanced healthcare materials, 2024)
The healing of diabetic wounds is hindered by various factors, including bacterial infection, macrophage dysfunction, excess proinflammatory cytokines, high levels of reactive oxygen species, and sustained hypoxia. These factors collectively impede cellular behaviors and the healing process. Consequently, this review presents intelligent hydrogels equipped with multifunctional capacities, which enable them to dynamically respond to the microenvironment and accelerate wound healing in various ways, including stimuli ‐responsiveness, injectable self‐healing, shape ‐memory, and conductive and real‐time monitoring properties. The relationship between the multiple functions and wound healing is also discussed. Based on the microenvironment of diabetic wounds, antibacterial, anti‐inflammatory, immunomodulatory, antioxidant, and pro‐angiogenic strategies are combined with multifunctional hydrogels. The application of multifunctional hydrogels in the repair of diabetic wounds is systematically discussed, aiming to provide guidelines for fabricating hydrogels for diabetic wound healing and exploring the role of intelligent hydrogels in the therapeutic processes. Multifunctional hydrogels have great advantages in the treatment of diabetic wounds. This review overviews hydrogels with stimuli‐responsive, injectable self‐healing, shape‐memory, conductive, and real‐time monitoring properties for application in treating diabetic wounds through strategies including antibacterial, anti‐inflammatory, immunomodulatory, antioxidant, pro‐angiogenic, and synergistic effects, providing guidelines for fabricating hydrogels exploring the role of intelligent hydrogels in the therapeutic process.